Antimicrobial Activity of Colistin Against Contemporary (2015 – 2017) P. aeruginosa and A. baumannii Isolates From a Chinese Surveillance Program - Zhang, Hui; Zhang, Ge; Zhang, Jingjia; Duan, Simeng; Kang, Yue; Yang, Qiwen; Xu, Yingchun (Frontiers in Microbiology, 2020)
Objective To investigate the incidence and susceptibilities of non-fermenting bacteria isolates from Chinese respiratory (RTI), intra-abdominal (IAI) and urinary tract (UTI) infections to antimicrobial agents between 2015 and 2017. Methods In total, 3,246 non-fermentative bacteria were collected from 21 hospitals and 9 hospital departments across 7 regions of China. A central testing laboratory was employed to determine antimicrobial susceptibilities using appropriate standards of interpretation. Results The majority of the isolates were Acinetobacter baumannii (n = 1,360, 41.9%) and Pseudomonas aeruginosa (n = 1,341, 41.3%). Overall multidrug resistance (MDR) and carbapenem resistance (CR) rates of Acinetobacter baumannii were 80.1 and 78.7% with MDR and CR rates in RTIs, IAIs, and UTIs of 82.0 and 81.0%, 82.6 and 81.0% as well as 53.1 and 46.9%. Overall MDR and CR rates of Pseudomonas aeruginosa isolates were 36.2 and 38.9% with 41.8 and 44.3%, 29.3 and 36.1% as well as 24.2 and 20.2% MDR and CR rates in RTIs, IAIs, and UTIs. Overall susceptibility rates to imipenem, meropenem, amikacin, ciprofloxacin, cefepime and piperacillin-tazobactam were 21.1, 21.3, 33.0, 18.4, 19.2, and 19.6% for Acinetobacter baumannii and 56.5, 58.5, 88.4, 63.1, 63.1, and 55.63% for Pseudomonas aeruginosa isolates, whereas for colistin they were 95.7 and 94.6%, respectively. In all departments and regions of China, susceptibility rates of Pseudomonas aeruginosa and Acinetobacter baumannii isolates to colistin were constantly above 80%. Conclusion Due to the high MDR and CR rates for Pseudomonas aeruginosa and Acinetobacter baumannii, isolates obtained from RTIs, IAIs, and UTIs only maintained high susceptibility rates to colistin between 2015 and 2017.